Synchronization of two forced double-well duffing oscillators with attached pendulums. - Brzeski, Piotr; Karmazyn, Anna; Perlikowski, Przemysław (Polskie Towarzystwo Mechaniki Teoretycznej i Stosowanej, 2013)
We investigate the dynamics of two coupled Duffing oscillators with attached pendulums forced kinematically by a common signal. Our attention is focused on different kinds of synchronization which can appear in the considered system. Different types of coupling (spring, damper and spring and damper simultaneously) are taken into account. We show in a two-parameters space (amplitude and frequency of excitation) existence of complete and phase synchronization and asynchronous ranges.
Keywords: Duffing pendulum system; bifurcational analysis; synchronization; oscylator Duffinga; system wahadłowy; bifurkacyjna analiza; synchronizacja; sprzężenie; różne rodzaje sprzężenia